Evolution of peritoneal dialysis technique failure from 2002 to 2017 in France. RDPLF data. - Benoît SCHWARTZ; Fatouma TOURE (RDPLF, 2018)
English Abstract In France, 6 to 7 % of patients with end stage renal failure are treated by peritoneal dialysis (1). Despite the annual augmentation of treated patients, it's still under public health goal. Peritoneal dialysis technique failure is one restraint of technique growth in France. The RDPLF collect data about technique survival and infections since 1986. Technique failure width is on restraint of PD growth. We used available data to describe trends in the different causes of technique failure to identify areas with feasible improvement to increase technical survival. Methods: This retrospective study includes public data from RDPLF over the 2002-2017 period. Results: More than 30% of treated patients experience technique failure each year and transfer to hemodialysis count for 33%. Main causes of HD transfer are inadequate dialysis, peritonitis, catheter dysfunction and fluid inadequacy. The study of technique failure causes trends shows a decreased mortality form 51% in 2002 to 38% in 2017 (p<0.05), an increase of transplantation access from 15% to 22% (p<0.05). Transfer to hemodialysis is stable 33% to 36% in the same period. The analysis au hemodialysis transfer shows a decrease of peritonitis from 22% in 2002 and 26% in 2004 to 13.6% in 2017 (p<0.05). It shows a light increase of catheter dysfunction from between 7-8% during 2002-2005 period, to 8.6-11.8% during 2013-2016 period (p>0.05). Conclusion: Technique failure causes evolved over the past fifteen years in France, there is an improvement in mortality and access to transplant, a decrease in peritonitis. Despite technique improvement and new PD solutions (Icodextrine based, biocompatible), there is still 10% of PD patients transferred each year to hemodialysis without favorable trends.